Peran Pesantren Dalam Peningkatan Sumber Daya Umat - Ahmad Abdul Rochim; Amal Khayati (CV. ULIL ALBAB CORP, 2023)
The purpose of this research is a form of concern for the efforts made by Islamic boarding schools as the oldest Islamic educational institutions in Indonesia, Islamic boarding schools are unique Islamic educational institutions, because their names are not taken from Arabic. And historically, pesantren with the role of kiai were considered to be the basis of community resistance against colonialists, so their existence was always monitored, their movements were restricted, their communication was hampered in order to strengthen the existence of this pesantren. So this research was conducted as a form of providing information to readers. This research method uses library research, namely content analysis which is an in-depth discussion collecting data in accordance with the discussion of the role of Islamic boarding schools in increasing the human resources. The result of this research is that educational institutions in Indonesia should follow the example of Islamic boarding schools which always play an active role in producing religious and moral students who are able to compete in the global era.